Bacteriological Surveillance of Ambulance Vehicles from a Tertiary Care Hospital of North India - Sharma, Shiwani; Datta, Priya; Gupta, Varsha; Vasesi, Dipanshu; Chander, Jagdish (Journal of Laboratory Physicians, 2021)
Objective An ambulance is a medically equipped vehicle which is used in case of any medical emergency for the transport of patients to treatment facilities. The ambulances help in the transportation of thousands of patients per year, and such patients may carry infectious microorganisms which pose a major threat to the treatment of such patients. In this study, we analyzed the extent of bacterial contamination in our ambulance vehicles and measured the degree of antimicrobial resistance among isolated pathogens.Material and Method This study included five ambulances of our tertiary care hospital and different random sites were swabbed in each vehicle. These were selected based on their well-known high frequency of contact by emergency personnel and patients. Swabs were inserted into sterile test tubes containing normal saline and immediately transferred to our microbiology laboratory to identify bacterial contaminants utilizing standard microbiological procedures.Result A total of 198 swab samples were collected from all the five ambulances, out of which 170 (85.8%) swabs were sterile and 28 (14.2%) swabs yielded potentially pathogenic bacterial isolates. The highest contamination rate with pathogenic bacteria was detected in the oxygen flow meter knob (60%), suction machine tubing (60%), and stethoscope (40%). Staphylococcus aureus (32%) was the most frequently detected microorganism.Conclusion Our study showed low prevalence of bacterial contamination in ambulances because of good infection control policy of our hospital, however, some areas still need improvement and require proper standard operating procedures of disinfection policies of these emergency vehicles.
Keywords: ambulance; disinfection; infectious microorganisms; multidrug resistant